Radiological Anatomy – Evaluation of Integrative Education in Radiology - Dettmer, S.; Schmiedl, A.; Meyer, S.; Giesemann, A.; Pabst, R.; Weidemann, J.; Wacker, F. K.; Kirchhoff, T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: Evaluation and analysis of the integrative course “Radiological Anatomy” established since 2007 at the Medical School Hannover (MHH) in comparison with conventional education.Materials and Methods: Anatomy and radiology are usually taught separately with a considerable time lag. Interdisciplinary teaching of these associated subjects seems logical for several reasons. Therefore, the integrative course “Radiological Anatomy” was established in the second year of medical education, combining these two closely related subjects. This interdisciplinary course was retrospectively evaluated by consideration of a student questionnaire and staff observations. The advantages and disadvantages of integrative teaching in medical education are discussed.Results: The course ratings were excellent (median 1; mean 1.3 on a scale of 1 to 6). This is significantly (p < 0.001) better than the average of all evaluated courses in the respective term (grade 2.8). The course improved the anatomical comprehension (90 %) and the students stated that the topics were relevant for their future medical education (90 %). Furthermore, interest in the subject’s anatomy and radiology increased during the course (88 %). According to the students’ suggestions the course was enhanced by a visitation in the Department of Radiology and the additional topic central nervous system.Conclusion: Integrative teaching of anatomy and radiology was well received by the students. Both, anatomical and radiological comprehension and the motivation to learn were improved. However, it should be considered, that the amount of work and time required by the teaching staff is considerably increased compared to traditional teaching.Key Points:Citation Format:
Keywords: anatomy education; diagnostic imaging utilization; undergraduate education; medical Schools